Leadless pacemakers as a new alternative for pacemaker lead‐related superior vena cava syndrome: A case report. Issue 9 (1st August 2022) - Curnis, Antonio; Milidoni, Antonino; Arabia, Gianmarco; Bontempi, Luca; Cerini, Manuel; Salghetti, Francesca; Ahmed, Ashraf; Ferraresi, Roberto; Mitacchione, Gianfranco; Mascioli, Giosuè
Abstract: Superior vena cava (SVC) syndrome is a rare disease induced by thrombosis and consequent occlusion of SVC, negatively affecting morbidity and mortality. The incidence of SVC syndrome from central venous catheters and pacemaker or defibrillator leads is increasing. Optimal treatment of pacemaker or defibrillator‐related SVC syndrome is not well defined. Lead extraction causes mechanical trauma to the vessel wall. In addition, subsequent device implantation on the contralateral side can be an added factor for venous occlusion. The use of leadless pacemakers could be an interesting option to reduce the risk of SVC restenosis after lead extraction. We report a clinical case of PM leads‐related SVC syndrome referred to our centers and treated with transvenous lead extraction, leadless pacemaker implantation and subsequent percutaneous angioplasty and stenting of the SVC and left innominate vein.